Dietary intervention in primary care: validity of the DINE method for diet assessment. - Roe, L; Strong, C; Whiteside, C; Neil, H; Mant, D (1994)
Primary health care staff are involved increasingly in the provision of dietary advice for health promotion, often without adequate training in nutrition assessment or counselling. At present no brief diet assessment methods are available which have been validated for this purpose in the UK. We report on the accuracy of the Dietary Instrument for Nutrition Education (DINE) in classifying dietary fat and fibre intakes. This structured questionnaire can be administered and scored in under 10 minutes by primary care staff without specialized nutritional knowledge, and includes a dietary counselling component. The classification of fat and fibre intakes as low, medium or high by the DINE method was compared to that of a detailed 4-day diet record in a population of 206 factory workers. There was exact agreement of categorization for 53% of fat intakes and 52% of fibre intakes, and only 6% of fat intakes and 5% of fibre intakes were grossly misclassified (placed in a high category by one method and a low category by another). Pearson correlation coefficients between the two methods were 0.51 for fat, 0.46 for fibre and 0.43 for the polyunsaturated:saturated fat ratio. The DINE method is a brief and inexpensive tool for diet assessment in primary care health promotion programmes.